Analisis Pengaruh Reward dan Punishment Terhadap Motivasi Pegawai di Pusat Pendidikan dan Pelatihan Perdagangan - Tien Danarti Mesra (Cendekia Niaga, 2020)
Serving, is the mission of government organizations which is one of the distinguishing characteristics of private organizations that are profit-oriented. Today, in such a competitive era, people need fast, precise, friendly, and professional services. This will be realized if every human resource in government organizations understands their respective duties and functions, has the motivation to serve and focuses on providing optimal performance to achieve common goals. Referring to this situation, it shows that human resources remain as the main key for the success of government organizations in providing services to the community. The importance of the role of human resources requires management in government organizations to have a strategy on how to manage, develop, maintain, and utilize them so that they can contribute optimally to the organization. One method that is often used in managing human resources is through the application of reward and punishment. The research method used is descriptive analysis with a quantitative approach, with the background of the objective is to explain the influence of the variables to be studied and then testing the hypotheses that have been formulated previously. The research variables are the reward variable (X1), the punishment variable (X2) as the influencing variable and the motivation variable (Y) as the influenced variable. The data collection method used was by distributing questionnaires and record documents. Analysis of the data in this study using multiple linear regression analysis processed using excel program. The results obtained from this study are the reward variable (X1) has a significant effect on the motivation variable (Y), on the other hand, the punishment variable (X2) has less effect on the motivation variable (Y).